Incidence of Venous Thromboembolism in Adults Receiving Extracorporeal Membrane Oxygenation: A Systematic Review. Issue 12 (19th March 2022) - Iannattone, Patrick A.; Yang, Stephen Su; Koolian, Maral; Wong, Evan G.; Lipes, Jed
Abstract : Extracorporeal membrane oxygenation (ECMO) has become an increasingly used tool for cardiorespiratory support. Thrombosis is a well-recognized complication of ECMO, yet the burden of disease remains unclear. We undertook a systematic review to investigate the incidence of venous thromboembolism (VTE) during ECMO or soon after decannulation, in patients screened for VTE. We retrieved all studies that evaluated VTE incidence in ECMO patients in EMBASE, MEDLINE, Web of Science, and Cochrane Library from inception to April 2, 2021. Studies reporting incidence of VTE diagnosed on systematic screening tests during ECMO or within 7 days of decannulation in adult patients were included. A total of 18 studies were included in the systematic review. These studies screened a total of 1095 ECMO patients. Most studies screened for cannula-associated deep vein thrombosis (CaDVT) after decannulation. The overall incidence of DVT was 52.8% (95% CI, 49.8–55.8%). Incidence of DVT was 53.5% (95% CI, 50.0–57.0%) for venovenous ECMO vs . 34.0% (95% CI, 26.5–42.2%) for venoarterial ECMO. No studies screened for pulmonary embolism. Our systematic review found a very high incidence of DVT among patients treated with ECMO. Routine screening for DVT after decannulation for all ECMO patients may be warranted.